2005
DOI: 10.1007/s10529-005-2727-4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mucosal Vaccine Against Foot-and-Mouth Disease Virus Induces Protection in Mice and Swine

Abstract: Epitopes of a foot-and-mouth disease virus (FMDV) capsid protein VP1 complex and a chimera of 6xHis-tagged cholera toxin B subunit (hCTB) were expressed in Hansenula polymorpha and used together as a mucosal vaccine. Antibody and cytokine responses to VP1-hCTB vaccine and protection against FMDV were evaluated by ELISA and a virus challenge test in mice, respectively. VP1-hCTB directly enhanced the expression of interleukin-5 (IL-5) both in serum and supernatants of cultured spleen cells. After challenging suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…For the practical application of a potential new rabies vaccine, five doses may not be acceptable, and many published studies have demonstrated successful intranasal immunization with less than three doses [1,25,26,29]. in our study, mice intranasally administered 3 times with crV/cT all died when intracerebrally infected with a lethal dose of virulent rabies virus, even though they showed some levels of anti-rabies virus ELisA antibodies and VNA (data not shown).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…For the practical application of a potential new rabies vaccine, five doses may not be acceptable, and many published studies have demonstrated successful intranasal immunization with less than three doses [1,25,26,29]. in our study, mice intranasally administered 3 times with crV/cT all died when intracerebrally infected with a lethal dose of virulent rabies virus, even though they showed some levels of anti-rabies virus ELisA antibodies and VNA (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…it is easier to vaccinate animals with the mucosal method than the parenteral method, and unlike parenteral vaccines, mucosal vaccination stimulates sigA production in mucosal tissues, which could effectively inhibit the entry of pathogens that invade their hosts via the mucosal route. The efficacy of mucosal immunization has been well documented for mucosal pathogens, such as influenza virus, Newcastle disease virus, foot and mouth disease virus, Aujeszky's disease virus, hiV and Ascaris suum [15,19,22,25,26,28,29,30]. Furthermore, mucosal immunization can also stimulate systemic immune responses, such as serum igG production and cytokine production by T cells [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above mentioned studies are essential for complete characterization of corn-derived CT-B and LT-B to be able to assess safety of the product. pathogens that have had important economic impact on the swine industry (Nilubol et al 2004, Song et al 2005, Maurer et al 2005, Verdonck et al 2005, Joensuu et al 2004). In addition to the economic loss that they cause, the prevalence of these infectious diseases raises concerns about pork safety.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a significant amount of work has been done on the development of mucosal protein of transmissible gastroenteritis virus (TGEV) in a pre-immunize-oral boosting study (Lamphear et al 2004) and intranasal and oral vaccination against foot-and-mouth disease (Song et al 2005) have indicated promising results for success of mucosal vaccination in pigs.…”
Section: 7mentioning
confidence: 99%